Riflessioni civilistiche in tema di ordine pubblico internazionale, maternità surrogata e arte della costanza (TEST BioLaw Journal - Rivista di BioDiritto, 2021)
With regard to international public order and surrogate motherhood, at least the Italian Courts of highest level consistently show great respect to the autonomy of the legislator and to the legal certainty.
Keywords: international public order; surrogate motherhood; medically assisted procreation; adoption; legal certainty